A DFT study of the electronic, optical, and mechanical properties of a recently synthesized monolayer fullerene network - Tromer, Raphael M.; Ribeiro, Luiz A.; Galvão, Douglas S. (Chemical physics letters, 2022)
Closely packed quasi-hexagonal and quasi-tetragonal crystalline phase of C60 molecules (named qHPC60) was recently synthesized. Here, we used GGA-PBE based DFT simulations to investigate the optoelectronic and mechanical properties of qHPC60 monolayers. qHPC60 has a moderate direct electronic bandgap, with anisotropic mechanical properties. Their elastic modulus ranges between 50–62 GPa. The results for optical properties suggest that qHPC60 can act as a UV collector for photon energies up to 5.5 eV since it presents low reflectivity and refractive index greater than one. The estimated optical bandgap (1.5–1.6 eV) is in very good agreement with the experimental one (1.6 eV). [Display omitted] •qHPC60 has a moderate direct electronic bandgap.•qHPC60 has anisotropic mechanical properties.•qHPC60 can act as UV collector for photon energies until 5.5 eV.•Estimated optical bandgap is in very good agreement with experiments.